Leptin, Leptin Soluble Receptor, and the Free Leptin Index following a Diet and Physical Activity Lifestyle Intervention in Obese Males and Females - Jeffrey E. Herrick; Gino S. Panza; Jared M. Gollie (Hindawi Limited, 2016)
Leptin (LEP) is associated with appetite regulation and metabolism. Concentration is linear with adiposity, suggesting LEP resistance. LEP circulates freely and bound with its soluble receptor (sOB-r); the ratio is the free leptin index (FLI), an index of leptin resistance; lower FLI suggests reduced biological action. Purpose. The aim was to determine the effect of changes in adipose tissue distribution on LEP, sOB-r, and FLI following 6 months (6 M) of a diet/exercise weight loss program (WLP). In addition, we aim to identify predictors of the FLI. Methods. 6 M WLP consisted of diet/lifestyle interventions following ADA guidelines. Body composition was assessed by DXA. LEP and sOB-r analysis were done via ELISA. Results. 10 adults completed the WLP. Significant reductions were seen in total fat percentage (% fat), nontrunk fat, (NTF), and trunk fat (TF) from base to 3 m and 6 M (p≤0.05). The FLI were reduced at 3 M and 6 M for males and 6 M for females. Total body fat and body weight predicted the FLI in both sexes. Conclusions. LEP and FLI reductions following 6 M of WLP were achieved independent of sOB-r changes. We also demonstrate that the FLI can be predicted noninvasively through total fat mass and body weight in kilograms.